A Review of Erosive Burning Models for Solid Propellant Rocket Motors (Spreadsheet) - Macêdo-Gonçalves, Daniel (Cranfield University, 2021)
This spreadsheet, an integral part of the thesis "A Review of Erosive Burning Models for Solid Propellant Rocket Motors" (Guided Weapon Systems MSc, 2020/2021), presents a useful tool in modelling the erosive burning rate of composite and double-base propellants, from modifications to the theoretical model originally proposed by Paul and Mukunda (1997).
Keywords: 'burning rate'; 'combustion instabilities'; 'turbulent boundary layer'; 'Non-automotive Combustion and Fuel Engineering (incl. Alternative/Renewable Fuels)'